PENGEMBANGAN DISCOVERABILITY PADA SISTEM DETEKSI BANJIR KIRIMAN MENGGUNAKAN PROTOKOL EDDYSTONE URL BERBASIS WEB OF THINGS - Geraldhi Aditya Putra Mahayadnya; Gusti Rafi Afkariansyah; Franciscus Faust Hartanto; Marshelino Laksmana Syahjaya; Harianto Harianto (Antivirus : Jurnal Ilmiah Teknik Informatika, 2021)
Internet of Things technology in post-flood handling systems in Indonesia has been widely applied. Several previous studies have shown several approaches in creating a post-flood detection system, including using SMS and using the Web that using the MQTT protocol. However, among the existing detection systems there is not yet a discoverability system to allow users to interact quickly with the system. In this study, a Web of Things-based post-flood detection system was created with the MQTT communication protocol and the Eddystone URL discoverability protocol. Web applications that used on the Web of Things use a Progressive Web App to enable compatibility with mobile devices. The test results show that the use of MQTT in the post flood detection system has a latency of less than 200ms, the use of Eddystone URL as a discoverability protocol in the flood detection system shows a fairly good system response with 90% success in ten trials on the Eddystone URL protocol, and web application testing with Google Lighthouse showed an average score of 91 for mobile web applications and an average value of 96.75 for desktop web applications.